2012
DOI: 10.1111/j.1654-1103.2012.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Community (re)organization in an experimentally fragmented forest landscape: insights from occupancy–scale patterns of common plant species

Abstract: Question How does experimental habitat fragmentation of a temperate Australian eucalypt forest affect local population patterns of common plant species 22 yr after landscape transformation to a pine plantation? Location Wog Wog Habitat Fragmentation Experiment, southeast Australia. Methods We use occupancy–scale relationships to examine the patterns of community organization of common understorey plant species in fragmented forests (small: 0.25 ha; large: 3.062 ha) relative to an intact native forest. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…At all but the largest dispersal scales, communities in small reserves tended to have composition determined by environmental conditions. Our results are consistent with findings from fragmentation experiments that (1) b diversity in old fields was greater among small fragments compared to within large fragments (Cook et al 2005) and (2) the distributions of common understory plant species became more aggregated over time within small forest fragments relative to distributions in continuous forest (Morgan and Farmilo 2012). In our study, temporal community turnover was greater in large reserves, albeit under limited conditions.…”
Section: Discussionsupporting
confidence: 82%
“…At all but the largest dispersal scales, communities in small reserves tended to have composition determined by environmental conditions. Our results are consistent with findings from fragmentation experiments that (1) b diversity in old fields was greater among small fragments compared to within large fragments (Cook et al 2005) and (2) the distributions of common understory plant species became more aggregated over time within small forest fragments relative to distributions in continuous forest (Morgan and Farmilo 2012). In our study, temporal community turnover was greater in large reserves, albeit under limited conditions.…”
Section: Discussionsupporting
confidence: 82%
“…Empirical studies have found inconsistent results about the effects of landscape spatial structure on plant communities, making it difficult to establish general patterns to apply to conservation management (Ewers andDidham 2006, Fahrig 2013). In some systems, increasing patch size and connectivity (which are generally correlated) have been shown to positively influence species richness (Harrison 1997, Damschen et al 2006, Morgan and Farmilo 2012, but negative responses have also been reported (Abadie et al 2011). In other cases, landscape spatial structure has been found to have no detectable impacts on plant communities and diversity has instead been explained primarily by other factors, such as local environmental variables (Dupre´and Ehrle´n 2002, Guirado et al 2007, Herrera and Laterra 2011.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that common species at WWHFE have increased in frequency within small forest fragments (Morgan & Farmilo ). In this study, it is apparent that ‘uncommon’ species are also responsive to fragmentation.…”
Section: Discussionmentioning
confidence: 95%
“…and shrubs (e.g. Hibbertia obtusifolia ), with extensive native leaf litter (Austin & Nicholls ; Morgan & Farmilo ). Exotic species are neither diverse nor abundant across the study site, and are evenly distributed throughout fragments and controls (B. Farmilo unpubl.…”
Section: Methodsmentioning
confidence: 99%